The Role of E-Commerce in the Business World - Tiara Purnama Sari , Yesa (Islamicate Institute, 2020)
This article discusses the role of e-commerce in the business world. The methods used in this study are literature methods sourced from books, reports, journals and websites. The findings of this article find: (1) The development of internet technology facilitates the way of doing business; (2) e-commerce is a place to buy and sell using social media; (3) this flatform has become a trend today that can facilitate buying and selling; (4) doing business using e-commerce is not hindered by distance and time; (5) e-commerce has a significant effect on the development of a business.